O‘ZBEK ADABIY TILI VA SHEVA MUNOSABATLARI - Mo‘minova, Sh.T.; Shofqorov, A.M. (SCIENCE and SOCIETY, 2023)
This article discusses the relationship between the Uzbek literary language and dialect, as well as the place and importance of dialectisms in literary works, i.e. fiction.